Global ID Coverage, Barriers, and Use by the Numbers : An In-Depth Look at the 2017 ID4D-Findex Survey - World Bank (World Bank, Washington, DC, 2020)
The ID4D-Findex data was collected as part of the 2017 round of the World Bank's Global Findex survey, carried out by Gallup, Inc. as part of its Gallup World poll. The survey was conducted on representative samples of the non-institutionalized civilian population over age 15.8 The survey included three questions related to ID that were asked in 97 countries: (1) whether or not a person had their country's national ID or equivalent foundational ID credential; (2) for those with the ID, whether they had used it for specific purposes; and (3) for those without the ID, what their reasons were for not having one. In five economies with no ID system or very limited coverage, people were asked a single question on whether or not they had been unable to access certain services due to lack of identity documents (see Annex 2 for full text of questions). Combined with other individual-level indicators from the 2017 Global Findex, these data provide new insights into who has an ID, how they are used, and persistent barriers to access. At the same time, the data have some limitations. First, while the ID4D-Findex questions cover countries that represent close the three-quarters of the world's population, they do not cover all countries. For example, most high-income countries, some low- and middle-income countries, and some smaller economies are not included. In total, the countries included in the ID4D-Findex data account for a little over 80 percent of the population in low and lower-middle income countries. Second, the Findex survey is limited to people ages 15 and older, and therefore does not capture the identity gap or correlates of identification for the youngest people. Importantly, we have restricted the analysis in this paper to those respondents who are above the age when the ID is mandatory, using information from the ID4D Global Dataset. In countries where the mandatory ID age is greater than 15 years old, excluding these observations provides more conservative estimates of the gap in identification than if they were included, as young people may not have an ID simply because they are not yet eligible or required to have one.